b - Centre for Policy Dialogue (Bangladesh) (b, 2018)
Articles on contemporary political and economic issues of Bangladesh.
In Bengali.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Politics and government -- 1971-